Summative evaluation of Caribbean integrated science projects - Reay, Judith F. (UNESCO, 1977)
This article describes the combined evaluation of two concurrent curriculum development projects--the Mona Project of the University of the West Indies (UWI) in Jamaica and the CEDO/UWI Caribbean Regional Science Project based at UWI, Barbados. The major strategy for summative evaluation was based on an educational experiment and upon achievement tests. There is little evidence that the data were used by decision makers and it is suggested that, in the end, decisions are taken on the basis of availability of published materials and individual appraisal of these
Keywords: Caribbean Regional Science Project